Synthesis of KAl(SO4)2 Solid Coagulants from Used Pots and Beverage Cans - Nanda Mustikarini; Ilma Fadlilah; Theresia Evila Purwanti Sri Rahayu (CHEESA: Chemical Engineering Research Articles, 2024)
Used pots and beverage cans are good sources of aluminum-rich raw materials for the synthesis of potassium aluminum sulfate (KAl(SO4)2), a solid coagulant. The synthesis process includes preparation, dissolution, extraction, sedimentation, and drying. Therefore, this research aimed to determine the characteristics of KAl(SO4)2 synthesized from aluminum pots and beverage cans waste, adjusted to the quality requirements of commercial KAl(SO4)2 according to SNI 06-2102-1991 standard. The materials used were aluminum pots, as well as a mixture of pots and beverage cans, with varying concentrations of 20%, 30%, and 40% KOH solvent. The synthesis results, characterized by XRF (X-ray fluorescence), showed an Al content of 0.001-3%. In addition, the results of the data analysis, adapted to SNI 06-2102-1991 standard for potassium aluminum sulfate, indicated that the synthesis met the required parameters for water-insoluble parts, Fe, Pb, and As, and Al2SO3, which was close to the quality requirements.